Value of serum GGT level in the timing of diagnosis of choledochal cyst perforation - Zhang, Shuhao; Cai, Duote; Chen, Qingjiang; Zhang, Yuebin; Chen, Ken; Jin, Yi; Luo, Wenjuan; Huang, Zongwei; Hu, Di; Gao, Zhigang (Frontiers in Pediatrics, 2022)
Background: Choledochal cyst perforation is extremely rare, and early diagnosis or prediction is important for the immediate therapeutic intervention of perforations. This study aimed to define the predictor(s) of an impending or complete spontaneous perforation of choledochal cyst and establish the optimal operative timing. Methods: All 429 consecutive choledochal cyst patients from January 2015 to December 2021, were included. A retrospective study was performed based on Kaplan-Meier analysis, and Cox univariate and multivariate analyses. Results: A total of 429 patients were included, among which, 21 had choledochal cyst perforations (group A), and 408 did not (group B). Compared to group B, the serum alanine aminotransferase, aspartate aminotransferase, direct bilirubin, gamma-glutamyl transpeptidase, indirect bilirubin, total bilirubin, and alkaline phosphatase were significantly higher in group A (p = 0.025, 0.006, < 0.0001, 0.0001, 0.001, < 0.0001, and 0.033). High serum gamma-glutamyl transpeptidase was negatively associated with perforation-free preoperative survival, and multivariate Cox regression revealed that serum gamma-glutamyl transpeptidase was an independent predictive factor for an impending or complete perforation (p = 0.042). Conclusions: A gamma-glutamyl transpeptidase level ≥ 346.5 U/L accompanied with significantly elevated liver enzymes and bilirubin levels was indicative of the possibility of an impending or complete choledochal cyst perforation, and a proactive surgical approach should be considered.